2006
DOI: 10.1088/0965-0393/15/2/004
|View full text |Cite
|
Sign up to set email alerts
|

A texture-component Avrami model for predicting recrystallization textures, kinetics and grain size

Abstract: The study presents an analytical model for predicting crystallographic textures and the final grain size during primary static recrystallization of metals using texture components. The kinetics is formulated as a matrix variant of the Johnson–Mehl–Avrami–Kolmogorov equation. The matrix form is required since the kinetic and crystallographic evolution of the microstructure is described in terms of a limited set of growing (recrystallizing) and swept (deformed) texture components. The number of components requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…temperature, impurities, initial size, texture, etc [38,39,41]. Our values and those reported in literature suggest a correlation between the initial grain size and the activation energy thus, the smaller the grain size, the lower the activation energy.…”
Section: Accepted Manuscriptsupporting
confidence: 78%
See 1 more Smart Citation
“…temperature, impurities, initial size, texture, etc [38,39,41]. Our values and those reported in literature suggest a correlation between the initial grain size and the activation energy thus, the smaller the grain size, the lower the activation energy.…”
Section: Accepted Manuscriptsupporting
confidence: 78%
“…In general, the grain growth occurs due to the movement of grain boundaries, where the boundary movement can be discontinuous, and change the direction of the motion unexpectedly. This activation enthalpy is related to the activation energy for boundary mobility which theoretically should be near to the self-diffusion energy although frequently that is not the case [36,38,39]. For example, for pure coarse-grained tungsten, the activation enthalpy for self-diffusion is within the range of 586-628 kJ/mol for single crystal, and 502-586 kJ/mol for polycrystalline tungsten [33], whereas the activation enthalpy for grain growth for a polycrystalline tungsten is 210.7±13.2 kJ/mol [36].…”
Section: Annealed Atmentioning
confidence: 99%
“…In the literature, several recrystallisation models can be found that are typically limited to specific thermomechanical conditions, focusing on simulating either static recrystallisation, see for example [8,9], or dynamic recrystallisation, see for example [10][11][12][13]. These models commonly adopt a purely phenomenological Avrami type formulation [14,15] or are based on a physically motivated recrystallised volume fraction evolution that is coupled to hardening related energy contributions.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain desirable mechanical properties of forged products, dynamic recrystallization (DRX), which affects the grain size distribution of final forging for metals with moderate-to-low stacking fault energy, is one of the most valuable microstructure evolution processes [1]. To simulate the microstructure evolution caused by DRX, many physical and empirical models have been developed [2][3][4][5][6][7][8]. In these studies, the traditional approach is based on empirical equations, such as the Johnson-Mehl-Avrami-Kolmogorov (JMAK) theory [9].…”
Section: Introductionmentioning
confidence: 99%